Education for health from a family environment - Melendez Chavez, Sendy (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
The objective of this work was to evaluate the results of the educational project in nursing students of reproductive health of nursing degree, period August 2021 January 2022, a mixed methodology was used, 66 students, 64 families participated. the result was that the students; They gave educational talks, addressed issues of cervical cancer prevention, breast cancer prevention, and prevention of sexually transmitted diseases, they felt confident, family members asked various questions, requested more topics of personal interest, and their experience was pleasant. teach and share information in the family environment.